Bilateral Subconjunctival Hemorrhage (SCH) Following Delivery - Kamal, Ronik Harsono; Dwinastiti, Yasmine Ayu (Vision Science and Eye Health Journal, 2024)
Introduction: Subconjunctival hemorrhage (SCH) occurs when blood enters from the conjunctival or episcleral blood vessels into the subconjunctival space. SCH is classified as traumatic and non-traumatic (NTSCH). Microvascular diseases and increased intraabdominal pressure are associated with NTSCH; consequently, SCH can develop after vaginal delivery. However, reports regarding postpartum SCH are still scarce. This study aims to enhance awareness and comprehension of postpartum SCHs rather than minimize their significance. Case Presentation: A 17-year-old female presented with bilateral redness in both eyes one day post-delivery with no other ocular complaints. There were no complications in pregnancy and labor. The patient had no medical history of anticoagulant usage, trauma, hypertension, or blood disorders. Ophthalmic examination revealed visual acuity 20/20 on both eyes and bilateral subconjunctival hemorrhage, while other examinations were unremarkable. Treatment included a cold compress for 24 hours, followed by warm compresses every two hours on both eyes. Pharmacological therapy included artificial tears and naphazoline eye drops. Conclusions: Increased intra-abdominal pressure during labor can contribute to SCHs. While spontaneous resolution is common, accurate differentiation of SCH etiology is crucial for effective management. Obstetricians and ophthalmologists must collaborate to identify risk factors early, including routine eye screenings during the perinatal period, to enhance patient comfort and safety. Furthermore, additional research endeavors and investigations are necessary to deepen our understanding of the frequency and risk factors associated with postpartum SCHs and to develop effective prevention and treatment measures.